Charismatic leadership in Islam : powerful position of Sufi Shaikhs in Bosnia - Aždajić, Dejan (Regnum Books International, 2019)
To understand Islam, one must understand the people who practice their faith. Consequently, this book is a detailed ethnographic study of two contemporary Sufi communities. It explores the perplexing range of theological and ritual variation, arguing for a direct correlation between Sufi multiformity and the agency of the spiritual leader, the Shaikh. He is principally responsible for shaping the community under his leadership